RISK ASSESSMENT OF EARLY POSTOPERATIVE COMPLICATIONS IN LAPAROSCOPIC SLEEVE GASTRECTOMY AND WAYS OF THEIR PREVENTION - Nazirov, F.G.; Khashimov, Sh.H.; Makhmudov, U.M.; Akbarov, M.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Optimization of the laparoscopic sleeve gastrectomy (LSG) technique for the prevention of perioperative complications in patients with morbid obesity. Materials and methods: The study included the results of treatment of 45 patients with morbid obesity who underwent LSG in 2014-2019 in the department of endovisual surgery. Among the patients, there were 35 women and 10 men (age 37,1±1,2 years; BMI 45,6±1,1 kg/m²). Results: Various complications associated with tactical and technical aspects during the LSG and the first 2 days after surgery were observed in 4 (8.8%) patients. The frequency of failure (leak) of the staple lines was 2.2% (1 patient), intra-abdominal bleeding and bleeding of the staple lines – in 4.4% (2 patients), bleeding from separated gastroepiploic vessels after mobilization of the stomach along the greater curvature in 2,2% (1 patient). It is noted that one of the most specific sections of the zone of interest when performing LSG and the likelihood of both intra- and postoperative complications is the proximal part of the stomach when mobilizing the latter, the gastroesophageal transition with the His angle, the proximal part of the “gastric sleeve” formed. For better endovisualisation of the stomach, calibration and determination of the longitudinal line of the stapled hardware suture, a special bariatric gastric bougie has been proposed for intraoperative intraluminal light curvature marking during LSG. Conclusions: LSG provides maximum weight loss (% EWL) = 83.2% 12 months after the intervention and a stable restrictive effect for 2-3 years after surgery, when the% EWL is not less than 94%. Bleeding from the stapler suture line and the inconsistency of the proximal segment of the formed gastric “tube” are the most formidable specific complications of LSG. The most important in terms of eliminating these complications are the timing of their diagnosis and timely decision-making on reoperation - relaparoscopy.